Improving Engine Oil Properties by Dispersion of hBN/Al2O3 Nanoparticles - Abdullah, Muhammad Ilman Hakimi Chua; Abdollah, Mohd Fadzli bin; Amiruddin, Hilmi; tamaldin, noreffendy; Mat Nuri, Nur Rashid; Hassan, Masjuki; Saleman, Abdul Rafeq (2014)
This paper provides oil properties study of conventional diesel engine oil enriched with hBN/Al2O3 nanoparticles. In this study, an optimal composition (0.5 vol.%) of hBN and Al2O3 nanoparticles separately dispersed in SAE 15W40 diesel engine oil by sonication technique. The oil properties were studied by measuring the Viscosity Index (VI), Total Acid Number (TAN), Total Base Number (TBN) and flash point temperature. The results reveal that the nano-oil with hBN nanoparticles could improves or at least maintain the key lubrication properties, though the TAN value is slightly increased. The results presented here may facilitate improvements in the conventional diesel engine oil performance.